Associations Between Adolescents' Perceptions of Alcohol Norms and Alcohol Behaviors: Incorporating Within-school Variability. Issue 2 (4th March 2017) - François, Amir; Lindstrom Johnson, Sarah; Waasdorp, Tracy E.; Parker, Elizabeth M.; Bradshaw, Catherine P.
ABSTRACT: Background : Social norm interventions have been implemented in schools to address concerns of alcohol use among high school students; however, research in this area has not incorporated measures of variability that may better reflect the complexity of social influences.Purpose : To examine the association between perceived alcohol norms, the student- and school-level variability of those norms, and alcohol use behaviors among high school students.Methods : A sample of 25 824 students from 58 high schools completed an online self-report survey. Hierarchical linear regression models were fit to examine the relationships between student- and school-level alcohol norm predictors, within-school variability, and current alcohol use and binge drinking.Results : Individual- and school-level norms were predictive of both current alcohol use and binge drinking. Whereas measures of norm diversity at the school level were not predictive of alcohol use behaviors, individual norm proximity was predictive of both current alcohol use and binge drinking.Discussion : The study findings were consistent with prior research and support assertions that variability measures should be incorporated into social norms research approaches.Translation to Health Education Practice : The findings support the incorporation of student-level variability measures, which could assist in identifying students who are susceptible to peer influence.